Changes in the gonad of female mudclan (Anodontia edentula) during maturation. - Morales, Jenny Lyn L.
Toothless clam, Anodontia edentula (Linneaus 1758) also known as mudclam belongs to Family Lucinidae, Class Bivalvia. A. edentula is considered a dioecious species with occasional occurrence of hermaphrodites in the population. the gametogenic cycle consists of several stages: developing (early and late), ripe, spawning, and spent. The study shows an increase in the sizes of follicles and oocytes and number of oocytes as maturation of the gonads occured from early to ripe stage and a decrease in the sizes of follicles and oocytes and number of oocytes from spawning to spent stage. In early developing stage mean follicle size is 159.5{ogon}38.9 um while mean oocyte size is 30.3{ogon}3.64 um. The follicles contained an average of 10{ogon}6.3 oocytes. during the late developing stage, follicles (500{ogon}30.2 um) and oocytes (48.9{ogon}4.4 um) increased in sizes. The number of oocytes reached an average of 13{ogon}5.14. In ripe ovaries , an average number of 26{ogon}6.42 oocytes with mean size of 60.3{ogon}4.8 um were found. These follicles have mean diameter of 457.5{ogon}24.3 um. the gonads started to decrease in size during spawning, oocytes have a mean diameter 50.1{ogon}5.1 um while the follicles have a mean size of 395{ogon}38.4 um. There was also an average of 9{ogon}2.31 large residual oocytes observed. In the spent stage the follicles (270.8{ogon}42.9 um) and oocytes (43.4{ogon}8.59 um) have further decreased in size. Small residual oocytes during the spent stage have also reduced in number (5{ogon}2.07 oocytes). The sizes of the gonads may depend on the duration of time since spawning took place.